Controversy Over Non-Madhhab Practices: A Critical Analysis of the Perspective of Ramadhan Al-Buthy about Contemporary Islamic Law - Hammad, Hamzah Abed Alkarim (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to thoroughly examine the dangers associated with not adhering to a specific madhhab in contemporary Islamic law from the perspective of Muhammad Sa'id Ramadhan Al-Buthy. In order to accurately achieve the study objective, a comprehensive examination of Al-Buthy’s critique concerning non-madhhab practices was carried out, with a primary focus on how these practices could disrupt legal interpretations and undermine the authority of Islamic jurisprudence. The analysis included the process of reviewing primary texts, scholarly commentaries, and secondary literature, all of which were carried out with the aim of accurately comparing the critique by Al-Buthy with other contemporary perspectives on the issue. The results showed that Al-Buthy strongly criticized non-madhhab movement for promoting subjective and inconsistent interpretations of Islamic law. The figure argued that this movement was capable of weakening the structured and scholarly tradition of Islamic jurisprudence. Furthermore, Al-Buthy emphasized that established madhhab played a very important role in preserving the integrity and continuity of Islamic legal principles, underscoring the dangers associated with abandoning these schools, including fragmentation and a lack of authoritative guidance. The critique of the observed figure typically emphasizes the risks of non-madhhab practices, such as the potential for division in Muslim community. This study makes a novel contribution by specifically focusing on Al-Buthy’s critique, which are often cited but not deeply analyzed in the context of non-madhhab movements. Specifically, the investigation situated the arguments of the observed figure in contemporary debates on the role of madhhab, thereby offering a fresh perspective on the relationship between traditional Islamic jurisprudence and modern legal challenges. The implications are particularly significant for scholars, legal practitioners, and policymakers in Islamic law, advocating for a renewed commitment to traditional legal frameworks to prevent the pitfalls of subjective interpretations associated with non-madhhab methodologies.